Blood Purification in Severe and Critical COVID-19 Patients: A Case Series of 5 Patients - Chen, Hongjun; Zhang, Leisheng; Zhang, Wei; Liu, Lili; Dai, Zhihua; Chen, Miao; Zhang, Donghang (Frontiers in Public Health, 2021)
Objective: The ongoing coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to a worldwide pandemic. Currently, supportive care measures remain the standard of care for severe and critical COVID-19 patients, such as ventilation oxygenation, fluid management and blood purification. In this study, we aimed to evaluate the effects of early blood purification therapy upon severe and/or critical COVID-19 patients. Patients and methods: From January 31, 2020 to March 1, 2020, a total 5 patients with COVID-19 (3 critical type cases and 2 severe type cases) received early blood purification treatment in the intensive care unit (ICU) of Affiliated Hospital of Zunyi Medical University. Clinical indexes, including oxygen concentration, blood gas analysis, oxygenation index, and laboratory test as well as disease scores were recorded and analyzed before and after the treatment with blood purification. Results: Among the 5 patients, 4 were males ranging from 35 to 80-year-old (Mean age=63±17.87). All cases with characteristics of OI<300mm Hg, decline in lymphocyte (LYMPH)%, boost in lactate dehydrogenase (LDH), troponin T (TNT), B-type brain natriuretic peptide (BNP), interleukin-6 (IL-6) and interferon-alpha (IFN-а), three with high flow nasal cannula (HFNC), two with non-invasive ventilation (NIV) and acute kidney injury (AKI), and one with shock and IV. Blood purification therapy significantly decreased the serum levels of inflammatory cytokine, ameliorated the concomitant symptoms and complications. Finally, one case was discharged from the hospital, 4 cases were transferred to the general ward, and all the 5 cases survived. Conclusion: Continuous blood purification therapy held promising prospects for alleviating the deteriorative progression of severe and critical types of COVID-19 in the early stage, together with ameliorating the accumulation of inflammatory cytokine and the concomitant symptoms and complications by efficacious immunoadsorption.